EDUKASI DAN PENDAMPINGAN KELUARGA PENDERITA DIABETES MELITUS DENGAN PENDEKATAN KELOMPOK PENDAMPING DIABETES SELF-MANAGEMENT EDUCATION (KP-DSME) - Wijayanti, Gusti Ayu Sri Puja Warnis; Mardiatun; Sulaiman, Ridawati (Poltekkes Kemenkes Mataram, 2025)
Diabetes mellitus (DM) is one of the major global health problems with a continuously increasing prevalence. Various epidemiological studies have shown a rising trend in the incidence of type 2 diabetes mellitus (T2DM) worldwide. The International Diabetes Federation (IDF) in 2021 estimated that 537 million adults aged 20–79 years worldwide are living with diabetes, representing 10.5% of the global population in that age group. This number is projected to increase to 643 million (11.3%) by 2030 and 783 million by 2045. These data emphasize the importance of implementing self-management strategies for individuals with diabetes. Effective diabetes control can be achieved through early prevention efforts by enhancing self-care abilities within the family level.This community service program aims to improve the knowledge and skills of people with diabetes in self-care management and to establish support groups that play a role in sustaining diabetes management at the community level. The methods implemented in this activity included health education and demonstration sessions related to diabetes self-care management.The results of this program indicated an increase in participants’ knowledge and skills regarding diabetes self-care and the establishment of self-care management support groups for people with diabetes. It is expected that the active roles of community health cadres, healthcare workers, and local governments will continue to strengthen sustainable diabetes self-management and control programs.